2008
DOI: 10.1007/s00572-008-0216-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the Glomeromycota by partial β-tubulin gene sequences

Abstract: The 3' end of the beta-tubulin gene was amplified from 50 isolates of 45 species in Glomeromycota. The analyses included a representative selection of all families except Pacisporaceae and Geosiphonaceae. Phylogenetic analyses excluded three intron regions at the same relative positions in all species due to sequence and length polymorphisms. The beta-tubulin gene phylogeny was similar to the 18S rRNA gene phylogeny at the family and species level, but it was not concordant at the order level. Species in Gigas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
1
31
0
2
Order By: Relevance
“…This is consistent with the phylogeny generated by the β-tubulin gene using an isolate of G. candidum from Maryland (Msiska & Morton 2009). Both of these studies were limited by using only a single sequence from a single spore of the new AM fungal species.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is consistent with the phylogeny generated by the β-tubulin gene using an isolate of G. candidum from Maryland (Msiska & Morton 2009). Both of these studies were limited by using only a single sequence from a single spore of the new AM fungal species.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, in G. clarum and G. manihotis the external mucilaginous layer reacts strongly in Melzer's reagent (pinkish-red to light purple), while the reaction of the same layer in G. candidum is very pale pink and only occurs in juvenile spores. Finally, molecular tools clearly identify that G. candidum is a member of Glomus group B, while G. diaphanum, G. clarum, and G. manihotis are in Glomus group A sensu Schwarzott et al (2001) (Msiska & Morton 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the SSU nrRNA gene also indicated that A. colombiana and an undescribed entrophosporoid species (WV201) nest within Acaulospora instead of as a unique monophyletic group (Walker et al 2004). Similarly A. colombiana and A. kentinensis evolved from different immediate ancestors based on a phylogeny of partial sequences of the b-tubulin gene (Msiska and Morton 2009). Thus gene phylogenies within Acaulosporaceae indicate the entrophosporoid mode of spore formation is not a synapomorphy that defines a unique monophyletic group.…”
Section: Discussionmentioning
confidence: 99%
“…The intrasporal variability in ribosomal DNA (rDNA) sequences (16,17,20,27) is sometimes much higher than the interspecific variation (7,25), and the phylogenetic overlap of sequences across species is a real problem with respect to identification. The use of protein-encoding genes for actin (15), tubulin (9,10,19), and P-type H ϩ -ATPase (9, 11) has already been investigated, but with limited success, while genes for ef1-alpha, V-H ϩ -ATPase, and F-ATPase ␤-subunit (30) seem efficacious only for discriminating between unrelated Glomus species. The expression profiles of a phosphate transporter (PT) gene of three Glomus species have been studied (4,18), and the gene was considered a promising avenue for the identification of AM fungi (13).…”
mentioning
confidence: 99%